Unveiling Male Hegemony: A Comparative Study of Nathaniel Hawthorne's The Scarlet Letter and Ahmad Tohari's Bekisar Merah - Olga A. Rorintulus (English Education Department, 2023)
This comparative study delves into the nuanced realms of women's resistance against male hegemony in two literary works from distinct cultural and temporal contexts: Nathaniel Hawthorne's